Brian Patrick McGuire: The Cistercians in Denmark. Their Attitudes, Roles and Functions in Medieval Society. (Cistercian Studies Series: Number Thirty-Five. Cistercian Publications, Inc. Kalamazoo, Michigan, 1982). 4215. - E. Green-Pedersen, Svend (Historie/Jyske Samlinger, 1987)
-